Motherhood experiences in the penitentiary unit Nº 33 of La Plata, Argentina - Cardozo, Mariela (2019)
This paper describes the exercise of motherhood among female prisoners in Unit No. 33 at the town of Los Hornos, (La Plata, province of Buenos Aires, Argentina). During 2016, practices and perceptions about motherhood and parenting were observed through a questionnaire that included open questions, as well as observations and informal talks in the pavilions.   It was possible to make the conflict visible that arises for female prisoners due to the deprivation of their freedom and the gender mandates associated with the “role” of being a mother. They were affected by the impact of their imprisonment on their children, and felt that they had abandoned their obligations by unprotecting those whom they had to take care of. They assumed the damage that their situation caused on the development of their children, whether they were inside or outside the prison.